2018
DOI: 10.3389/fimmu.2018.02746
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis: Classical vs. Paradoxical. The Yin-Yang of TNF and Type I Interferon

Abstract: Chronic plaque psoriasis is a common debilitating skin disease. The identification of the pathogenic role of the TNF/IL-23/TH17 pathway has enabled the development of targeted therapies used in the clinic today. Particularly, TNF inhibitors have become a benchmark for the treatment of numerous chronic inflammatory diseases such as psoriasis. Although being highly effective in psoriasis treatment, anti-TNFs can themselves induce psoriasis-like skin lesions, a side effect called paradoxical psoriasis. In this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
114
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(123 citation statements)
references
References 133 publications
(136 reference statements)
4
114
0
5
Order By: Relevance
“…The activated neutrophils are recruited into the stratum corneum in the early stage and they create focal aggregates, called Munro’s microabscesses [31]. The enhancement of TNF-α and IL-17 signaling in the psoriatic plaque drives the neutrophil accumulation into the inflamed skin area, activating keratinocytes to release chemokine (C-X-C motif) ligand (CXCL)1, CXCL2, CXCL3, CXCL5, and IL-8 [32]. In turn, neutrophils produce reactive oxygen species (ROS), IL-17, cathelicidin, and neutrophil extracellular traps (NETs) as proinflammatory signals to reduce the inflammation.…”
Section: Molecular Pathogenesis Of Psoriasismentioning
confidence: 99%
“…The activated neutrophils are recruited into the stratum corneum in the early stage and they create focal aggregates, called Munro’s microabscesses [31]. The enhancement of TNF-α and IL-17 signaling in the psoriatic plaque drives the neutrophil accumulation into the inflamed skin area, activating keratinocytes to release chemokine (C-X-C motif) ligand (CXCL)1, CXCL2, CXCL3, CXCL5, and IL-8 [32]. In turn, neutrophils produce reactive oxygen species (ROS), IL-17, cathelicidin, and neutrophil extracellular traps (NETs) as proinflammatory signals to reduce the inflammation.…”
Section: Molecular Pathogenesis Of Psoriasismentioning
confidence: 99%
“…С этим может быть связана недостаточная эффективность терапии или развитие НЛР, в том числе «парадоксальных», на фоне лечения ГИБП. В качестве примера можно привести осложнение фармакотерапии ингибиторами ФНОα, определяющееся как «парадоксальный» псориаз, связанный, как полагают, с активацией ИФН-зависимого врожденного иммунного ответа, на фоне блокирования физиологических иммунорегуляторных эффектов ФНОα [102,103]. Следует принимать во внимание и иммуногенность ГИБП, индуцирующих синтез антилекарственных антител, которые могут приводить к «вторичной» неэффективности ГИБП [104].…”
Section: таблицаunclassified
“…The pathogenesis of this reaction remains unclear. It has been suggested that interferon-α overproduction by plasmacytoid dendritic cells, increased number of interleukin (IL)-17/IL-22 secreting Th17 cells and IFNsecreting Th1 cells may play a crucial role (4,5).…”
Section: Possible Paradoxical Photosensitive Psoriasis Induced By Tummentioning
confidence: 99%